Peran Metode Ilmiah Dalam Mengembangkan Pendidikan Fisika - I Ketut Mahardika; Adinda Citra Badarsila; Ernasari Ernasari; Miftakhun Nikmah Royani; Rojabita Dwirgahayu Nurhidayat; Sri Handono (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
The scientific method is a systematic and structured approach used to gather data, observe natural phenomena, and develop scientific understanding. The scientific method helps students in developing critical thinking skills, problem-solving abilities, and a deep understanding of physics concepts. This article explains how the scientific method can be integrated into physics education to create a learning environment focused on experiments, observations, and data analysis. This method also encourages learners to develop research skills and think creatively. Developing a physics curriculum based on the scientific method can enhance students' interest in science and prepare them to face challenges in our increasingly interconnected and science-based society. This article is based on the results of previous related journal reviews, which provide a research foundation and in-depth information about the role of the scientific method, and it then links it to physics education.